Pengenalan Konsep Matematika pada Anak Usia Dini melalui Lagu - Sri Rahmawati Fitriatien; Ninik Mutianingsih; Restu Ria Wantika; Liknin Nugraheni; Eko Sugandi (Universitas Lancang Kuning, 2020)
The comprehension concept of number and geometric shape in early childhood is needed to develop children's interest to mathematic. Introducing the concept of number and geometry in early childhood is first step of learning mathematic so the learning process is more fun and children do not scared of mathematic. To motivate children's favorite level to mathematic, the devotion team of Study Program Mathematic Education at PGRI ADI BUANA Surabaya do assistance activities to PAUD mother in Gondang, Mojokerto with the aim to introducing mathematical concept in early childhood through song. The song was chosen by devotion team as an alternative learning media because it was based on the result discussion with PAUD mother community when the team survey state that through song it was able to give pleasure to children. This activity consist of 10 devotion teams that consist of 5 lecturers and 5 students with 28 PAUD mothers in Gondong, Mojokerto. The result achieved from this dedication activity are able to contribute to PAUD mother in creating poetry and song lyric related to mathematical concept. The program sustainability plan is to register the copyright of the song by PAUD mother as intelectual property.